ANALISIS GAYA KEPEMIMPINAN DAN KOMUNIKASI ANTARPRIBADI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada Telesales Officer Divisi Telemarketing PT. AXA Mandiri Financial Services Di Jakarta) - Putri, Rifqi Amri (Jurnal Manajemen Magister Darmajaya, 2018)
All companies generally have a strategy to advance the company, it requires good communication skills between superiors and subordinates to avoid misunderstandings. In addition to good communication skills between superiors and subordinates in an organization, the ability of superiors to lead an organization is also needed. Leadership is important in every organization, because this is the leader factor that determines the success or failure of an organization, therefore the company must be able to optimize the performance of its employees, company performance will achieve satisfactory results in the company if there is good communication, effective leadership and motivation good work too. With good performance, the company will be able to compete in the industry. This study aims to determine how much the relationship between leadership style, interpersonal communication on employee job satisfaction and its effect on employee performance. The method used in this study is path analysis with the help of SPSS version 21. The results of this study indicate that the relationship of leadership style to employee job satisfaction has a contribution of 0.24, the relationship of leadership style to employee performance has a contribution of 0.279, the relationship between interpersonal communication and satisfaction employee work has a contribution of 0.131, the relationship of interpersonal communication to employee performance has a contribution of 0.448, the relationship of employee job satisfaction to employee performance has a contribution of 0.185. While for the total influence between leadership style through employee job satisfaction on employee performance has a contribution of 0.323 and interpersonal communication through employee job satisfaction on employee performance has a contribution of 0.472Keywords — leadership style, interpersonal communication, employee job satisfaction, employee performance